Could Emergency Diseases Surveillance Systems Be Transitioned to Routine Surveillance Systems? A Proposed Transition Strategy for Early Warning, Alert, and Response Network - Asghar, Rana Jawad; Abubakar, Abdinasir; Buliva, Evans; Tayyab, Muhammad; Elnossery, Sherein (Frontiers in Medicine, 2022)
In humanitarian emergencies, traditional disease surveillance systems either don’t exit to start with or come under stress due to huge influx of internal or external migrants. However cramped camps, with unreliable supply of safe water and weak sanitation systems are ideal setting for any major outbreak. Early Warning, Alert and Response Network (EWARN) have been supported by WHO since the late 1990’s to ensure health system capacity to identify risks and control them early before they become major epidemics. These systems have been proven to be an excellent asset in reducing morbidity and mortality in humanitarian crisis around the world. However, there is also a global challenge of transitioning them back to a regular or national surveillance system in their respective countries. This article is result of in country consultations arranged by Eastern Mediterranean office of the World Health Organization. In these consultations’ different countries unique local conditions and limitations were discussed to identify a way forward of transitioning emergency disease surveillance systems into regular systems. Different options were presented which could be further modified according to local needs. As there has not been any documented evidence of a successful transition of any emergency surveillance system, it is difficult to discuss or determine the gold standard for transition. As with any public health program being practiced in the field, local decision making with some broad guidelines will be the best approach available. This article provides these guidelines and practical steps which could be further modified according to country needs.